Anxiety Scores in Caregivers of Children with Hypoplastic Left Heart Syndrome. (20th June 2016) - Caris, Elizabeth C.; Dempster, Nicole; Wernovsky, Gil; Butz, Catherine; Neely, Trent; Allen, Robin; Stewart, Jamie; Miller‐Tate, Holly; Fonseca, Rachel; Texter, Karen; Nicholson, Lisa; Cua, Clifford L.
Abstract: Objectives: Caring for children with congenital heart disease places significant stress on caregivers. Minimal data exist evaluating stress levels in caregivers of children with hypoplastic left heart syndrome (HLHS). The goal of this study was to obtain baseline stress scores for caregivers of children with HLHS and determine if associations exist between scores and specific caregiver factors. Study Design: A cross‐sectional study using a web‐based survey targeted towards caregivers of children with HLHS was performed. Baseline demographics of the caregiver and child with HLHS were obtained. Caregivers completed three validated questionnaires including the Pediatric Quality of Life Inventory (PedsQL), Parenting Stress Index‐ Short Form (PSI‐SF) and the Pediatric Inventory for Parents (PIP). Results: Four hundred fifty‐nine caregivers completed at least one questionnaire. PSI‐SF total score was 80.5 ± 23.1 (> 86 = significant stress), PIP frequency total score was 119.0 ± 37.2, and PIP difficulty total score was 118.1 ± 35.7. Lower quality of life was significantly correlated with higher scores on the PSI‐SF ( r  = −0.6), the presence of a developmental issue in the child ( r  = 0.3) as well as higher scores on the PIP frequency ( r  = −0.5) and difficulty scales ( r  = 0.4). Other demographic values for the caregiver and child did not significantly correlate with PSI or PIP total scores. Conclusions: Anxiety/stress scores of caregivers with children with HLHS are correlated with how well the child is perceived to be doing physically and developmentally by the caregivers. Caregivers with physical and/or developmental concerns may need added psychosocial support.